Sensory Visualization: A Writing Strategy for Students - Carolyn R. Fehrenbach (The Advocate, 2011)
This paper describes the use of a Sensory Visualization strategy to engage secondary pre-service teachers in a writing activity integrating current or historical events through the modality of the senses. Students write papers from the viewpoint of a person in an event after viewing a photograph or illustration of the event.